Perlindungan terhadap Pencipta atas Penggunaan Judul Lagu Bertaut Karya Nadin Amizah sebagai Judul Film Bertaut Rindu - Khansa Nailah Ramadhini; Anne Gunawati; Jarkasi Anwar (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The development of the music and film industry in Indonesia shows the relationship between one creative work and another. This raises a problem, especially the use of the song title Bertaut by Nadin Amizah as the title of the film Bertaut Rindu. This problem is related to copyright protection, as regulated in Law Number 28 of 2014 concerning Copyright. This study will examine two problems, namely how the creator's legal protection for the use of the song title Bertaut which is used without permission as the title of the film Bertaut Rindu based on the Copyright Law and how the production house Sinemart is responsible for the use of the film title Bertaut Rindu based on the Copyright Law using two theories of legal protection and the theory of responsibility with normative juridical research methods, through a statute approach and a case study. The data used consists of primary data and secondary data obtained through literature studies and document and field studies, then analyzed qualitatively. The results of the research are that Nadin Amizah does not allow the title of Bertaut's song to be used as the title of the film Bertaut Rindu even though the word Bertaut is found in the KBBI. However, Nadin Amizah wants the song Bertaut to be used in Nadin Amizah's film, which is in Article 5 of the UUHC regarding the moral rights of protection and can be achieved through a warning or summons in Article 95 of the UUHC.